Dietary Supplementation with Pioglitazone Hydrochloride and Resveratrol Improves Meat Quality and Antioxidant Capacity of Broiler Chickens - Fan Zhang; Chenglong Jin; Shiguang Jiang; Xiuqi Wang; Huichao Yan; Huize Tan; Chunqi Gao (Applied Sciences, 2020)
The study aimed to investigate the effects of pioglitazone hydrochloride (PGZ) and resveratrol (RES) on yellow-feathered broiler chickens. A total of 500 broiler chickens were randomly divided into four groups and fed a basic diet (control group) or a basic diet supplemented with 15 mg/kg PGZ, 400 mg/kg RES, or 15 mg/kg PGZ plus 400 mg/kg RES for 28 days. Compared with the control group, the PGZ and PGZ plus RES groups presented a significantly higher average daily gain and a decreased feed-to-gain ratio. Increases in the dressing percentage, semi-eviscerated yield, muscle intramuscular fat content, and C18:1n-9c, C18:3n-6, C20:3n-3, and monounsaturated fatty acid (MUFA) percentages were found in the PGZ plus RES group. Moreover, the diet supplemented with RES or PGZ plus RES increased the activities of catalase, glutathione peroxidase, and superoxide dismutase, and decreased the levels of reactive oxygen species of thigh muscle. Additionally, the mRNA abundance of peroxisome proliferator-activated receptor γ coactivator 1α, fatty acid-binding protein 3, nuclear factor erythroid-2-related factor 2, and superoxide dismutase 1 was increased in the PGZ plus RES group. In conclusion, this study suggested that dietary supplementation of PGZ combined with RES improved the growth performance, the muscle intramuscular fat content, and antioxidant ability of yellow-feathered broiler chickens.